Cryo-EM meets crystallography: A model-independent view of the heteronuclear Mn 4 Ca cluster structure of photosystem II - Jimin Wang (Proceedings of the National Academy of Sciences, 2025)
Photosynthesis converts solar energy to chemical energy by splitting water molecules and carbon dioxide to produce oxygen and carbohydrates with an efficiency that engineers working on solar energy device can only dream of. Photosystem II (PSII) is the enzyme that catalyzes the light-driven oxidation of water that occurs during photosynthesis. This oxygen-producing reaction occurs in the Mn 4 Ca cluster found inside the enzyme’s oxygen-evolving center (OEC). Even though the structure and mechanism of action of the OEC have been intensively investigated for many decades, questions still remain about both. The Mn 4 Ca cluster stores the high-energy oxidizing equivalents required for water oxidation so that its own oxidation state depends on its chemical composition, i.e., the number of its oxygen ligands. The issue addressed here is the number of oxygen ligands associated with the Mn 4 Ca cluster after PSII has been exposed to two of the four flashes of light necessary for it to produce an oxygen molecule, PSII 2F. Comparisons of recently published cryo-EM maps and crystallographic OEC-omit maps described here reveal the OEC structure of PSII 2F contains only five internal oxygen ligands, and that the sixth O ligand identified earlier in PSII 2F crystal structures is an artifact caused by model bias. This finding should have a significant impact on our understanding of the mechanism of water oxidation that is catalyzed by PSII because it is incompatible with prevailing high valence paradigm (HVP) models for this process.